Pastoral and woodcutting activities drive Cedrus atlantica Mediterranean forest structure in the Moroccan Middle Atlas. Issue 2 (March 2016) - Coudel, Marc; Aubert, Pierre‐Marie; Aderghal, Mohammed; Hély, Christelle
Abstract: Human activities are historical ecological drivers, and we need to better understand their effects on ecosystems. In particular, they have been very important in the shaping of the Mediterranean biodiversity hotspot. Researchers and managers nonetheless lack knowledge concerning the impacts of their combinations and their current intensity on the structure of forest ecosystems of the southern part of the Mediterranean basin. In this study, we have develped a new methodology in order to understand the impacts of combined pastoral and woodcutting activities on the forest structure of the still ill‐described but ecologically and economically important Moroccan Middle Atlas cedar forests. In a 40 000 ha forest, we chose 103 sites and sampled human activities through proxies and forest structures through circumference and vertical structures. A typology of sites yielded four human activity types: dominant pastoral activities, dominant oak cutting or cedar cutting activities, and an intermediate mid‐disturbance type. This typology did not depend on altitude or substrate, confirming that the ecosystem structures linked to the different types depend more on human activities than on main environmental parameters. Pastoral activities modified forests the most, converting them to parklands with reduced canopies and low dynamics but high tree maturation. Woodcutting activities induced gap dynamics, favoring Cedrus atlantica in favorable environmental conditions and Quercus ilex otherwise, while they affected vertical structure depending on the local environment and competition for light and soil resources. Moderately disturbed stands showed forest maturation with low competition for light. Unlike previous studies, we found no evidence of a general degradation of cedar forests due to local human activities. However, cedar logging has reduced standing basal area regionally and one third of the sites may have vulnerable cedar populations due to pastoral activities and to unfavorable environmental conditions. These results can direct future research and management needs for a better protection of Mediterranean forests and parklands and their biodiversity, although to be effective such efforts must also partner with sociogeographical studies.